Affliction - Lim, Cordelia Ni Jie (2015)
Affliction is a collaborative effort between Geraldine and I. It is a mixed media film that portrays a pregnant woman’s fears and psychological stress being manifested in the form of nightmares experienced by her unborn child. Through moments of live action depicting the silhouette of a pregnant woman struggling at fearful noises and thunderous sounds around her, the film transits into an abstract stop-motion scene inside her womb where the fetus faces several situations of violence and danger. Utilizing a mix of back-lit plasticine stop motion and visual effects, the abstract film takes viewers through different stages of fears and struggles by both mother and child. The aim of Affliction is to portray transient, surrealistic images and dynamic movements, thus creating new dimensions that invites viewers to contemplate on an otherwise hidden conflict - the unseen torture and anxiety felt by pregnant women and their child as a result of emotional abuse.